2008
DOI: 10.1002/jsfa.3400
|View full text |Cite
|
Sign up to set email alerts
|

Effect of conjugation with glucosamine on the functional properties of lysozyme and casein

Abstract: BACKGROUND: Modification with carbohydrates usually changes the functional properties of proteins. Such modification might make non-conventional food proteins (such as plant and microbial proteins) more applicable for human consumption. The purpose of this research was to conjugate glucosamine to lysozyme and casein using a water-soluble carbodiimide and to investigate the effect of conjugation on the functional properties of these proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 50 publications
2
23
0
Order By: Relevance
“…The diffused bands in SDS-PAGE further confirm the formation of conjugated products with wide distribution of molecular weights. Similar results have been reported by other investigators 9,[15][16][17][18][19][20] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The diffused bands in SDS-PAGE further confirm the formation of conjugated products with wide distribution of molecular weights. Similar results have been reported by other investigators 9,[15][16][17][18][19][20] .…”
Section: Discussionsupporting
confidence: 92%
“…Destruction of the outer membrane of Gramnegative bacteria is a result of strong surface activity of the conjugated lysozyme, which might enhance the lytic activity of lysozyme toward peptidoglycan layer in the inner membrane. Due to the improvement of lysozyme dextran solubility at different pH values and better emulsion and foam stability, lysozyme dextran is a suitable candidate for antimicrobial activity 15,20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the studies conducted by Aminlari et al (2005) the increased incubation time may be the reason for the disassociation of glycans from the protein molecules. There is another possibility that the interaction between proteins will increase and compete with the conjugation between proteins and glucose or xanthan gum molecules (Ramezani et al 2008). The highest degree of glycosylation (71.1 %) was obtained with SPI:G of 1:2 after 6 h incubation (50°C, 65 % relative humidity).…”
Section: Resultsmentioning
confidence: 99%
“…In general, high protein solubility is preferred for further optimization of protein functionalities (Kinsella 1979). The literature information showed that protein solubility can be increased by Maillard reaction (Aminlari et al 2005;Liu et al 2011;Paraman et al 2007;Xie and Hettiarachchy 1997;Ramezani et al 2008). All glycosylated SPIs (at pH of 7) showed significantly (p<0.05) increasing solubility after glycosylation incubation from 0 to 24 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in some cases, glycation also induces altered functional properties which are not innate to the enzyme in question. Altered functional properties induced with glycosylation include increased aqueous solubility, enhanced emulsifying and foaming properties, with the latter two being of an importance in food science [8]. Specificity can also be altered, e.g.…”
Section: Introductionmentioning
confidence: 99%